Mutagenicity test of magnetic nanocomposite for interface fixation. (30th September 2016) - Luo, Xinle; Zhu, Weimin; Cui, Jiaming; Chen, JieLin; Peng, Liangquan; Xiong, Jianyi; Xu, Weili; Zeng, Yanjun; Wang, Daping
The aim of the study is to evaluate the biocompatibility and safety of the Nano-HA/PLLA/Fe2 O3 magnetic composites material from toxicological aspects for the clinical use of the interface fixation, produce the Nano-HA/PLLA/Fe2 O3 magnetic composites material and its diffusion, and examine the diffusion through Ames test. The observation markers of the test are the mutagenic rates (MRs) of murine typhoid salmonella. The results of MR are less than 2 in the experimental groups of all dosage levels. The Nano-HA/PLLA/Fe2 O3 magnetic composites material will not cause the increase of the back mutation in the MTS. It indicates that this artificial bone will not cause gene mutation.